Bacterioplankton abundance and heterotrophic production from the Chatham Rise, east of New Zealand, measured during the SalpPOOP (TAN1810) campaign onboard the RV Tangaroa - Fenella Deans; Moira Décima (PANGAEA, 2025)
Heterotrophic bacterioplankton abundance and production was sampled from six to eight depths in the euphotic zone on the SalpPOOp voyage off the east coast of New Zealand in October/November 2018. Duplicate 1.5 ml samples were collected for cell abundance measurements. Samples were preserved with 15 μl of 25% Glutaraldehyde for assessing pico- and nano-phytoeukaryote and heterotrophic bacterioplankton abundances. Samples were kept in the dark for 15 minutes at lab temperature (>8 °C) before being flash-freezing in liquid nitrogen and stored at -80°C. Samples were subsequently analysed on a Beckman-Coulter CytoFLEX S flow cytometer. Bacterioplankton heterotrophic production was estimated from the incorporation of tritiated leucine using the centrifugation method (Smith and Azam, 1992). Triplicate subsamples and one control of 1.2ml seawater were added to labelled microcentrifuge tubes, with 120 μl of 50% trichloroacetic acid (TCA) added to the controls. The samples and control tubes all received an addition of 40 nM of 3H-Leucine (Perkin-Elmer, specific activity = 150.1 Ci mmol-1), and were then incubated for two hours in the dark in on-deck incubators at in-situ temperature for 20 m depth at that station. The incubations were ended by the addition of 120 μl of 50% TCA to fix the sample, with the samples then stored at -20C before processing on land following the procedure outlined in Gasol (1999). All microcentrifuge tubes were vortexed before being spun on a centrifuge for 10 minutes at 12000 g followed by aspiration of the liquid from the sample. The microcentrifuge tubes then had 1 ml of 5% TCA added, before being vortexed and spun for another 10 minutes at 12000 g. The tubes were aspirated for a final time before the addition of 1 ml of scintillation cocktail and a final vortex. From this point the samples were stored in the dark at room temperature. The incorporated radioactivity of each sample was determined by running the tubes on a Tri-Carb® Liquid Scintillation Counter (Perkin-Elmer) with quenching correction. The resulting scintillation values were used to calculate the incorporated Leucine, and from this the bacterial uptake of carbon (Gasol, 1999). Salp sampling was carried out using double oblique net tows from a depth of 200 meters to sea surface, employing a 0.7-meter diameter Bongo frame fitted with two 200-micron mesh nets. Each net was equipped with a General Oceanics flow meter to quantify the volume of water filtered, along with a temperature-depth recorder. Sampling was performed at least twice daily (day and night) with filtered volumes typically ranging from 150 to 500 m?^3. Collected salps were identified to the species level using established taxonomic references (Foxton, 1965; doi:10.1017/S0025315400016519; Bone, 1998), then categorized as either oozooids or blastozooids, and measured for total length, which was then corrected to oral-to-atrial length (OAL). For biomass estimations, individuals of Salpa thompsoni were grouped into 5-mm bins. Abundances were calculated for each size class, and biomass was estimated based on these length-frequency distributions following the methodology of Iguchi and Ikeda (2004). Additional methodological details can be found at doi:10.1594/PANGAEA.928092